Characteristics Of Neurogenic Shock Resulting From Spine Injury - Widya Islamiyah Tahir; Achmad Harun Muchsin; Fadillah Maricar (Sean Institute, 2023)
Neurogenic shock is a distributed shock characterized by loss of sympathetic tone due to acute spinal cord or central nervous system injury. Cervical spine injury, spinal anesthesia, Guillain-Barre syndrome, and transverse myelitis are among the causes of neurogenic shock. Neurogenic shock describes the sudden loss of autonomic tone due to Spinal Cord Injury (SCI). Disruption of the descending sympathetic pathway causes opposing vagal tone in vascular smooth muscle to decrease systemic vascular resistance and vasodilation. Hypotension resulting from neurogenic shock places patients at increased risk of spinal cord ischemia secondary to impaired autoregulation. Neurogenic shock occurs due to damage to the spinal cord above the 6th thoracic vertebra. There are no definitive diagnostic tests, but classically patients present with relative hypotension and bradycardia